THE MAIN FACTORS OF PREPARING YOUNG PEOPLE FOR FAMILY LIFE (TAMADDUN NURI JURNALI, 2024)
This article describes the main factors of preparing young people for family life. Also, the research conducted on the topic was analyzed.